8. CHANGES IN ENERGY CONSUMPTION DURING TRAINING OF ATHLETIC ATHLETES AND SWIMMERS (Vietnam Journal of Community Medicine, 2023)
Objective: Assess the total energy needs during the general and professional preparation phases (total energy consumption) for national athletic athletes and swimmers. Subjects and methods: Cross-sectional descriptive study with analysis. This research evaluates the Total Energy Expenditure (TTEE) in track and field athletes participating in sprints, jumps, and throw events (2 men, 3 women), as well as swimmers specializing in sprint and medium-length events (3 men, 2 women) in Ho Chi Minh City National Sports Training Center in February 2023. Heart rate monitoring devices were employed to assess the Exercise Energy Expenditure (ExEE) during professional training. Additionally, the study employed methods to calculate Basal Metabolic Rate (BMR) and Physical Activity Level (PAL). Energy consumption was calculated during the first 10 days of both the general and specific preparation phase. Results: In the athletics team, there was a significant increase in ExEE from 684.46 kcal (SD = 324.5) during the general preparation phase to 936.12 kcal (SD = 636.3) in the specific preparation phase (Sig = 0.007*). TTEE also rose from 2795.7 kcal (SD = 494.5) to 3062.66 kcal (SD = 802.1) (Sig = 0.005*). In contrast, swimmers displayed a slight but statistically insignificant rise in ExEE from 2981.08 kcal (SD = 843.45) to 3237.88 kcal (SD = 751.9) and TTEE from 4811.86 kcal (SD = 941.5) to 5068.34 kcal (SD = 864.6) (Sig = 0.094). Conclusion: The swimming team required greater energy for their training process compared to the track and field athletes.
Keywords: Nutrition, Energy consumption, Energy needs, Swimmers, Athletics.